EFFECT OF ADVERTISING AND PERSONAL SELLING ON TOYOTA AGYA BUYING INTEREST (Studies on Customers of PT. Agung Automall Branch of Baganbatu) - Rumapea, Yeni Pebriani; Heriyanto, Meyzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at PT. Agung Automall Baganbatu Branch, located on Jl. Lintas Riau- North Sumatra, Bahtera Makmur Village, Kec. Bagan Sinembah, Kab. Rkan Hilir, Riau. The purpose of this study was to determine the effect of advertising and personal selling on buying interest in Toyota Agya (sudi on customers of PT. Agung Automall, Baganbatu Branch). Advertising and personal selling (X1X2) meanwhile buying interest (Y).The research method used is quantitative descriptive analysis obtained from the results of a questionnaire measured by a Likert scale which is then processed by the SPSS program. The sample of this study was 58 respondents from the population who were calculated using the Slovin formula. This study uses a simple linear regression analysis method and multiple linear regression analysis.The results showed that advertising had an effect on buying interest in Toyota Agya with t count> t table (11,445> 2.00324) and significance (0.000 <0.05). Personal selling has an effect on buying interest in Toyota Agya with t count> t table (3,449> 2.00324) and significance (0.001 <0.05). Advertising and personal selling on Toyota Agya purchase interest with F count> F table (78,076> 3.16) with significance (0.000 <0.05). It can be concluded that advertising and personal selling have a positive and significant effect on buying interest in Toyota Agya at PT. Agung Automall Branch of Baganbatu.Â Keywords: Advertising, Personal Selling, Purchase InterestÂ